(untitled) (Medico Legal Update, 2020)
A large quantity of India‘s population is reduced to destitution because of high coverage health-care expenses and also suffering from antagonistic consequences of poor health care services. India has accomplished several gains in the field of Health since the new millennium, such as, life expectancy at birth has increased, the infant mortality and maternal mortality ratio has fell down and the spread of contagious diseases such as HIV/AIDS has been controlled etc. Again WHO, recently officially declared India free from maternal and neonatal tetanus and also polio free. But at the same time, among the five BRICS Nations, namely (Russia, Brazil, South Africa, China and India), India is considered as the poorest performer on the health indicators. India has failed to sufficiently protect its citizens against poor quality of health care as well as financial risks associated with health expenditure. Health Care Industries of a Country can play crucial roles not only in providing quality care and improving access to medicines for the citizens, but also in developing economic growth of the Country. Again, as it is universally accepted that Health is magnificent and efficacious investment for the economic growth of a Nation, this paper will analyze several major challenges that India need to be addressed, most notably the poor and ineffective regulation of the country, the rapid growth of commercialization of health care services, inadequate public expenditure along with very low level of public expenditure. Here the approach of Judiciary towards the various challenges surrounding the health care services in India will also be discussed.